Impact of the Stress on the Sub-Micron N-Metal Oxide Semiconductor Field Effect Transistor Characteristics - R. Marrakh; A. Bouhdada (Active and Passive Electronic Components)
In this paper, we present a drain current model for stressed short-channel MOSFET's. Stress conditions are chosen so that the interface states generated by hot-carriers are dominant. The defects generated during stress time are simulated by a spatio-temporal gaussian distribution. The parasitic source and drain resistances are included. We also investigate the impact of the interface charge density, generated during stress, on the transconductance. Simulation results show a significant degradation of the drain current versus stress time.